RNF219 interacts with CCR4–NOT in regulating stem cell differentiation. (26th October 2020) - Du, Hao; Chen, Chen; Wang, Yan; Yang, Yang; Che, Zhuanzhuan; Liu, Xiaoxu; Meng, Siyan; Guo, Chenghao; Xu, Manman; Fang, Haitong; Wang, Fengchao; Lin, Chengqi; et al.
Abstract: Regulation of RNA stability plays a crucial role in gene expression control. Deadenylation is the initial rate-limiting step for the majority of RNA decay events. Here, we show that RING finger protein 219 (RNF219) interacts with the CCR4–NOT deadenylase complex. RNF219–CCR4–NOT exhibits deadenylation activity in vitro . RNA-seq analyses identify some of the 2-cell-specific genes and the neuronal genes significantly downregulated upon RNF219 knockdown, while upregulated after depletion of the CCR4–NOT subunit CNOT10 in mouse embryonic stem (ES) cells. RNF219 depletion leads to impaired neuronal lineage commitment during ES cell differentiation. Our study suggests that RNF219 is a novel interacting partner of CCR4–NOT and required for maintenance of ES cell pluripotency.